Mennesket i verden - som brud - Heggem, Synnøve Sakura (Grundtvig-Studier, 2007)
Mennesket i verden - som brud [Human being - as bride] By Synnøve Sakura Heggem Grundtvig’s distinctive renewal and continuation of a traditional briderhetoric as a means of expressing his perception of mankind’s position in the world lends itself, as here, to an evaluation in terms of gendered discourse. We meet the bride-figure with many varying faces: the Nordic goddess Freja in the role of bride of Christ; the young singing bride; the old bride; the bride as a microcosm relative to others and the world; as man and as priest in a concrete church-political sermon; as mother, daughter and sister; and not least as the Daughter of God. Grundtvig attributes to her certain traits of weakness but no unworthy qualities - first and foremost because the bride is a desirable and loving creature; secondly because Grundtvig challenges both bride and bridegroom alike, in his rhetoric about the human being in the world. In the struggle against evil in the world and within the human creature, Grundtvig constantly claims the necessity of concentrating upon goodness, truth and beauty in humanity. Only in light of the loving and beloved human being, can evildoing be discovered and to some extent healed. This viewpoint shapes a bride-rhetoric of a specific humane and Christian character.